Laboratory Diagnostic Challenges in Resource-Limited Settings: Current Practices, Quality Gaps, and Future Directions (Sahel Journal of Life Sciences FUDMA, 2026)
Precise laboratory diagnosis is essential for patient safety, illness surveillance, and efficient healthcare delivery. Nonetheless, laboratories in several resource-constrained environments still encounter enduring difficulties that impact test outcomes' accessibility, quality, turnaround time, and dependability. Inadequate infrastructure, erratic power supplies, reagent and consumable shortages, limited equipment maintenance capacity, staff shortages, ineffective specimen referral systems, and a lack of quality management system adoption are common obstacles. Diagnostic errors, delayed clinical decision-making, inadequate antimicrobial stewardship, and decreased efficacy of public health measures are all consequences of these difficulties. This narrative review summarises current laboratory diagnostic practices in resource-limited settings and examines key barriers across the total testing process (pre-analytical, analytical, and post-analytical phases). It draws attention to deficiencies in quality assurance, such as inadequate internal quality control, irregular involvement in external quality evaluation, and partial compliance with laboratory accreditation regulations. Practical improvement techniques are also included in the report, including the expansion of point-of-care testing backed by strong governance, staff development, equipment standardization, reinforced supply chains, and the gradual deployment of quality management. Lastly, new possibilities are explored as means to increase coverage and quality, such as integrated diagnostic networks, digital health tools, and connection solutions. To improve clinical results and achieve universal health care, laboratory systems must be strengthened through sustained funding and quality-focused changes.